Implementation of E-Business in Realizing Green Banking in Sustainable Islamic Banking: A Literature Study - Melisa Putri; Muhammad Iqbal Fasa (Scimadly Publishing, 2024)
Digital transformation in the banking industry has driven the implementation of e-business as a primary strategy in realizing green banking, especially in Islamic banking based on the principles of sustainability and fairness. Digitalization through internet banking, mobile banking, and electronic payment systems enables operational efficiency, reduced use of physical resources, and reduced carbon footprint. In addition to increasing financial inclusion, e-business also strengthens transparency and transaction security. However, its implementation faces various challenges, such as digital infrastructure readiness, data security risks, and adaptation to Islamic regulations. Therefore, a comprehensive strategy and policy support are needed to ensure that this transformation is in accordance with Islamic principles and supports sustainability goals. The success of e-business integration in green banking in Islamic banking is highly dependent on technological readiness, supportive regulations, and awareness and active participation from various stakeholders. With proper implementation, Islamic banking can not only increase its competitiveness in the digital era, but also contribute to a more inclusive, efficient, and environmentally friendly financial system. Therefore, further research is needed on the most effective policies and business models to ensure that digitalization in Islamic banking is in line with the principles of green banking and long-term sustainability.